(untitled) (Proceedings of the Mongolian Academy of Sciences, 2019)
In the presentreport we look intosynthesized silver and gold-containing nanocomposites based on humic substances. The composition and properties of humic substances isolated from brown coal in Mongolian deposits have beenestablished. The methodology of obtaining platinum-containing nanobiocomposites using a matrix of humic substances is described. Our investigation shows thattheir composition and structure are characterized by a complex of modern physicochemical methods, such as X-ray, energy dispersive spectral microanalysis, infrared spectroscopy (IR), ultraviolet spectroscopy (UV), X-ray diffraction analysis, Scanning electron microscopy (SEM).